2019
DOI: 10.1021/acs.energyfuels.9b01034
|View full text |Cite
|
Sign up to set email alerts
|

Study of Mercury-Removal Performance of Mechanical–Chemical-Brominated Coal-Fired Fly Ash

Abstract: The mechanical–chemical-modified fly ash (FA-MC) and mechanical–chemical-brominated fly ash (FA-MC-Br) were prepared by omnidirectional planetary ball mill, and impregnated–brominated fly ash (FA-I-Br) was also prepared using the same mass ratio of fly ash/NH4Br as a comparison. The mercury-removal efficiency of raw fly ash (FA), FA-MC, FA-MC-Br, and FA-I-Br was evaluated in a fixed-bed reactor. The physical and chemical properties of the four samples were investigated by the Brunauer–Emmet–Teller, scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…To date, activated carbon injection (ACI) is considered to be the most commercialized technology for controlling mercury emission from coal-fired flue gas. , However, its high operational cost and low utilization rate limit its wide application. , To improve it, attention has been focused on chemical modification besides the carbon-based adsorbent, in which sulfur modification, such as SO 2 , elemental sulfur, plasma-carrying sulfur, etc., reveals a promising way to improve Hg 0 removal ability. Metal oxides have many advantages over activated carbon, such as wide reaction temperature, potential regeneration, and low cost .…”
Section: Introductionmentioning
confidence: 99%
“…To date, activated carbon injection (ACI) is considered to be the most commercialized technology for controlling mercury emission from coal-fired flue gas. , However, its high operational cost and low utilization rate limit its wide application. , To improve it, attention has been focused on chemical modification besides the carbon-based adsorbent, in which sulfur modification, such as SO 2 , elemental sulfur, plasma-carrying sulfur, etc., reveals a promising way to improve Hg 0 removal ability. Metal oxides have many advantages over activated carbon, such as wide reaction temperature, potential regeneration, and low cost .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research showed that MC bromine-modified fly ash is an economic and efficient adsorbent for mercury removal . The main forms of mercury after adsorption saturation are HgBr 2 and HgO, which are easy to leach in the process of secondary utilization and lead to secondary release.…”
Section: Methodsmentioning
confidence: 99%
“…Because the composition of fly ash is extremely complex, eliminating the influence of various components of fly ash is beneficial for obtaining the mercury MC stabilization mechanism. Furthermore, SiO 2 is the main component of MC bromine-modified fly ash developed in previous studies, which accounts for 47.72%. , To this end, HgBr 2 was loaded into SiO 2 by the impregnation method to prepare simulated adsorption saturated MC bromine-modified fly ash (SFA). The method for preparing SFA was carried out according to the following steps: (1) due to the good solubility of mercuric bromide in ethanol, 0.5 g of mercuric bromide (99.5% purity; Sinopharm Chemical Reagent Co. Ltd.) was added to 10 mL of ethanol (95% purity) and dissolved to prepare solution#1; (2) 1 mL of solution#1 was added to 79 mL of ethanol and diluted to prepare solution#2; (3) 10 g of silicon dioxide (99% purity; Sinopharm Chemical Reagent Co. Ltd.) was added into solution#2 and then stirred for 6 h by a magnetic stirrer at room temperature; (4) the impregnated sample was put in the oven and dried at low temperature (60 °C) until the weight difference between the two measurements was less than 1%, and thus, SFA was finally obtained.…”
Section: Methodsmentioning
confidence: 99%
“…The abundant O ad would facilitate Hg 0 oxidation to generate HgO as the active species. The related reaction process was described by eqn (4)- (6). As the efficiencies of the raw catalyst and pure CeO 2 were no more than 38.3%, the superior performance of the CeO 2 modied commercial SCR catalyst was also primarily resulted from the synergy of V 2 O 5 and CeO 2 in the catalyst.…”
Section: No Removal Performance Of the Ceo 2 -Scr Catalystsmentioning
confidence: 99%
“…Hg 2+ and Hg p can be respectively captured by wet ue gas desulfurization (WFGD) and particulate matter control device (PMCD) of power plant because of their physical properties, while Hg 0 is difficult to be controlled by the single pollutant control equipment due to its volatility and water insolubility. 5,6 So the key to the control of mercury emission from coal combustion power plant is the removal of Hg 0 . Similarly with mercury, NO x is also a sort of hazardous contaminant with great harm to environment that coal burning releases, and NO occupies about 95% among NO x .…”
Section: Introductionmentioning
confidence: 99%